Nasoseptal chondroprogenitors isolated through fibronectin-adherence confer no biological advantage for cartilage tissue engineering compared to nasoseptal chondrocytes - Jovic, Thomas H.; Thomson, Emman J.; Jones, Nick; Thornton, Catherine A.; Doak, Shareen H.; Whitaker, Iain S. (Frontiers in Bioengineering and Biotechnology, 2024)
demonstrated an affinity for trilineage differentiation by first passage and the expression of stem/progenitor cell markers increased significantly from digest to first passage (CD29, 44, 49e, 73 and 90, p<0.0001). No significant differences were seen in adhesion or growth rates. Collagen and aggrecan gene expression was higher in FACs than CDCs (2-fold higher, p=0.008 and 0.012 respectively), but no differences in chondrogenic potential were seen in any cell mixtures in 3D culture models.The fibronectin adhesion assay does not appear to reliably isolate a chondroprogenitor cell population from nasoseptal cartilage, and these cells confer no advantageous properties for cartilage tissue engineering. Refinement of cell isolation methods and chondroprogenitor markers is warranted for future nasoseptal cartilage tissue engineering efforts.